EFFECT OF ENTREPRENEURSHIP EDUCATION ON THE ENTREPRENEURIAL INTENTIONS OF VOCATIONAL HIGH SCHOOL STUDENTS THROUGH SELF-EFFICACY AS MEDIATION VARIABLES - Putrianna; Eryanto, Henry; Usman, Osly (Faculty of Economics and Business, Universitas Negeri Jakarta, 2023)
This study was conducted to determine the effect of entrepreneurship education on the entrepreneurial intention of SMKN 2 Sukabumi students through the mediating variable of self-efficacy. The research method used is a quantitative research method with a descriptive approach. The population used in this study were students of SMKN 2 Sukabumi class XI, and XII from all majors, namely AKL, BDP, OTKP, RPL, and TKJ consisting of 948 students and students with a sample of 255 students referring to Isaac and Michael's table. This research model uses a path analysis model and the data analysis technique used is SEM (Structural Equation Modeling) using the SmartPLS version 3 application. From the results of the study, it can be seen that entrepreneurship education has a positive and significant effect on entrepreneurial intentions and self-efficacy. However, self-efficacy cannot mediate the relationship between entrepreneurship education and entrepreneurial intentions